Biochemical Markers of Bone Turnover in Patients with β-Thalassemia Major: A Single Center Study from Southern Pakistan. (23rd February 2016) - Sultan, Sadia; Irfan, Syed Mohammed; Ahmed, Syed Ijlal
Abstract : Objectives . Skeletal complications in β -homozygous thalassemic patients are uncommon but often debilitating, even amongst children and adolescent patients with well maintained transfusion and chelation therapy. The aim is to evaluate the biochemical markers of bone turnover in regularly transfused thalassemic patients and its possible correlations with demographic data and hematological and biochemical markers. Methods . In this prospective cross-sectional study, 36 β -thalassemia major patients were enrolled from March 2012 to March 2014. All patients underwent complete blood counts, LFTs, serum ferritin, serum calcium, phosphorus, serum albumin, alkaline phosphatase, 25-OH vitamin D, and parathormone (PTH) levels. Results . There were 17 males and 19 females with mean age of 12.56 ± 5.9 years. Hypocalcemia and hypophosphatemia were seen in 66.6% and 19.4%, respectively, while 25-OH vitamin D deficiency was present in 72.2% of thalassemic children and adolescents. Hypoparathyroidism was seen in 13.8% while hyperparathyroidism was detected in 8.3% of patients. There was direct correlation between serum phosphorus and ferritin levels (P < 0.05 ). No correlation was found between indirect bilirubin and skeletal parameters, calcium and parathyroid hormone (P > 0.05 ). Conclusions . Biochemical profile is significantly altered in patients with β -thalassemia major and bone associated biochemical abnormalities like hypocalcaemia, 25-OH vitamin D deficiency, and hypophosphatemia are not uncommon in Pakistani patients with thalassemia major.